2021
DOI: 10.2478/ijhp-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

Online learning during the Covid-19 pandemic: the experiences and perceptions of undergraduate occupational therapy students at two Australian universities

Abstract: Purpose To investigate if first-year occupational therapy students who have had no on-campus, face-to-face learning experiences differed from second-, third- and fourth-year students in their perceptions and experiences of online learning during the Covid-19 pandemic. Methods One hundred and fifty-one occupational therapy undergraduate students (80.8% female; 66.2% 20–24 old) completed the Student Engagement in the e-Learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 48 publications
0
8
0
3
Order By: Relevance
“…The findings indicated that students found the constant struggle of placement and educational workloads, while trying to stay safe and caring for others particularly challenging. This had a psychological impact of anxiety, stress, low motivation and decreased social interaction that was reflected in previous research [ 3 , 50 52 ]. This research took place during the third lockdown in the United Kingdom situated in the winter months (February-March 2021) possibly adding to the demotivated feelings reported.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The findings indicated that students found the constant struggle of placement and educational workloads, while trying to stay safe and caring for others particularly challenging. This had a psychological impact of anxiety, stress, low motivation and decreased social interaction that was reflected in previous research [ 3 , 50 52 ]. This research took place during the third lockdown in the United Kingdom situated in the winter months (February-March 2021) possibly adding to the demotivated feelings reported.…”
Section: Discussionmentioning
confidence: 83%
“…While clinical placement was undertaken during this period, an element of uncertain and last-minute changes was apparent. This differed from international experiences where clinical placement was postponed [ 10 ] or replaced by telehealth approaches and simulated exercises [ 50 ]. The delivery of placement was challenging on the part of those involved in its organisation and facilitation, and generated worry and anxiety with students.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda que a pandemia seja enfrentada e vivenciada de modo particular e desigual em cada país, estudos mostraram que os programas educacionais no mundo todo, tradicionalmente oferecidos na modalidade presencial, tiveram que ser temporária e rapidamente adaptados para o ensino remoto [3][4][5][6][7][8] . Mudanças nos modos de ensino que tradicionalmente levariam meses ou anos para serem discutidas e implementadas foram sendo planejadas, aprendidas e desenvolvidas ao mesmo tempo, dada a ruptura com os encontros presenciais.…”
Section: Introductionunclassified
“…Mudanças nos modos de ensino que tradicionalmente levariam meses ou anos para serem discutidas e implementadas foram sendo planejadas, aprendidas e desenvolvidas ao mesmo tempo, dada a ruptura com os encontros presenciais. Nesse contexto, há uma rara oportunidade e necessidade de explorar os impactos de tais mudanças 8 .…”
Section: Introductionunclassified
See 1 more Smart Citation